The GbsR Family of Transcriptional Regulators: Functional Characterization of the OpuAR Repressor - Ronzheimer, Stefanie; Warmbold, Bianca; Arnhold, Christian; Bremer, Erhard (Frontiers in Microbiology, 2018)
Accumulation of compatible solutes is a common stress response of microorganisms challenged by high osmolarity; it can be achieved either through synthesis or import. These processes have been intensively studied in Bacillus subtilis, where systems for the production of the compatible solutes proline and glycine betaine have been identified, and in which five transporters for osmostress protectants (Opu) have been characterized. Glycine betaine synthesis relies on the import of choline via the substrate-restricted OpuB system and the promiscuous OpuC transporter and its subsequent oxidation by the GbsAB enzymes. Transcription of the opuB and gbsAB operons is under control of the MarR-type regulator GbsR, which acts as an intracellular choline-responsive repressor. Modeling studies using the X-ray structure of the Mj223 protein from Methanocaldococcus jannaschii as the template suggest that GbsR is a homo-dimer with an N-terminal DNA-reading head and C-terminal dimerization domain; a flexible linker connects these two domains. In the vicinity of the linker region, an aromatic cage is predicted as the inducer-binding site, whose envisioned architecture resembles that present in choline and glycine betaine substrate-binding proteins of ABC transporters. We used bioinformatics to assess the phylogenomics of GbsR-type proteins and found that they are widely distributed among Bacteria and Archaea. Alignments of GbsR proteins and analysis of the genetic context of the corresponding structural genes allowed their assignment into four sub-groups. In one of these sub-groups of GbsR-type proteins, gbsR-type genes are associated either with OpuA-, OpuB-, or OpuC-type osmostress protectants uptake systems. We focus here on GbsR-type proteins, named OpuAR by us, that control the expression of opuA-type gene clusters. Using such a system from the marine bacterium Bacillus infantis, we show that OpuAR acts as a repressor of opuA transcription, where several compatible solutes (e.g., choline, glycine betaine, proline betaine) serve as its inducers. Site-directed mutagenesis studies allowed a rational improvement of the putative inducer-binding site in OpuAR with respect to the affinity of choline and glycine betaine binding. Collectively, our data characterize GbsR-/OpuAR-type proteins as an extended sub-group within the MarR-superfamily of transcriptional regulators and identify a novel type of substrate-inducible import system for osmostress protectants.